An Evaluation of English Learning Materials for Information and Technology Students Department at Politeknik Negeri Padang - Indri Astuti (Postgraduate School, Universitas Negeri Padang, 2019)
This study aimed to get the criteria for English language teaching materials needed by Padang State Polytechnic Information and Technology students and evaluate English teaching materials that were used to determine the level of compatibility of teaching materials used with criteria obtained in terms of language, content, and methodology. This research was an evaluation research. Questionnaires, interviews, and analysis formats were used to obtain data. The results of data analysis showed that: (1) criteria for English language teaching materials were needed by students majoring in Information and Technology in terms of language indicated that the teaching material used was in accordance with the needs of students, majors, and their level of English; in terms of the content of teaching material used had an emphasis on speaking and listening skills and teaching materials used for writing and reading were still lack; in terms of the methodology of teaching materials used were equipped with activities that train speaking skills so that training and assignments were focused on practicing speaking skills. (2) The level of compatibility of teaching material in terms of language was 58%. (3) The level of compatibility of teaching material in terms of contents, namely 42%. (4) The level of compatibility of teaching materials used in terms of methodology was 42%. Based on the results of the study, it could be concluded that students majoring in Information and Technology needed material that could improve their listening and speaking skills, then the material used in writing and reading was further reproduced.